Developing Guided Inquiry-Based Science Student Worksheet to Improve Student’s Science Process Skills and Learning Outcomes on Thematic Learning of Maintaining the Health of Human Respiratory Organs in Elementary Schools - Dahri Novan; Suratno Suratno; A. Sapriati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
In Science learning in elementary school, the guided inquiry has commonly been implemented to train students to discover Science phenomena. This research aimed to analyze the process, outcomes, and effectiveness of implementing a Science student worksheet based on guided inquiry. The design employed was descriptive-quantitative. The research involved 79 fifth grade students of SDN Bangsalsari 02 in Jember. The data analyses, which was carried out in a descriptive qualitative manner, was in the form of an interview with the students, the questionnaire, and the students’ learning outcomes. The test involved a large group class containing 39 students and a small gorup class containing 40 students. There were prêt-test and post-test given to both the small gorup and the big group. The experimental study used 12 children in the small gorup and 39 children in the big group. The research instrument consisted of a questionnaire, interview, observation, pre-test and post-test. The analysis was done by testing validity, practicality, effectiveness, normality, homogeneity, and t-test. The result of the research showed that the Guided-Inquiry-based Science Student worksheet that had been developed was valid, practical, and effective. The level of validity based on the validation results is 79.5%, the level of practicality based on implementation validation is 81.0%, the effectiveness level for improving science process skills is 94.82%, and the effectiveness level for improving learning outcomes is 95%. It can improve the science process skills and learning outcomes on the thematic learning of maintaining the health of human respiratory organs on the students of SDN Bangsalsari 02 Jember, Indonesia.